Pengaruh Strategi Pemasaran KPR BNI Terhadap Kepuasan Pelanggan di Kota Manado (PT. Bank Negara Indonesia (Persero), Tbk.Cabang Manado) - Yohanes Koyong, Albert; A. F. Kalangi, Johny.; F. C. Walangitan, Olivia (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract. PT. Bank Negara Indonesia (Persero), Tbk Branch Manado is one of the largest national banks in North Sulawesi and even Indonesia. At the moment the banking sector in Indonesia entered a period of very competitive competition, the banking sector has a strategic role in contributing to the economic growth of a country. Investment, consumer credit, mortgage is one of them. Investors in the region or the world see the huge potential of the credit markets, especially on the types of consumer credit in Indonesia due to the large number of people in Indonesia. Property and real estate sectors, in Indonesia, is one of the largest business or industry, it can be said in Asia. So that the marketing strategy mortgages offered customers expected liking so as to give satisfaction. The method used is the analysis method for the quantitative description of the relationship that consists of a variable mortgage marketing strategy BNI is a variable that is used to view customer satisfaction. Application of marketing is a business strategy in target markets to maintain customer satisfaction. Analysis technique used is the Simple Linear method is to determine the effect of KPR BNI marketing strategy to customer satisfaction. Based on the results of this research is that KPR BNI Marketing Strategy (X) Influential significantly to customer satisfaction (Y). So in creating customer satisfaction, the company should be able to increase the Marketing Strategy. The better the assessment of the debtor, the higher the satisfaction. Keywords: KPR BNI Marketing Strategies and Customer Satisfaction.